Dietary inclusion of defatted black soldier fly larvae meal: impacts on laying hen performance, egg quality, serum biomarkers, and intestinal morphology - Chen, Lifei; Sun, Haoyang; Song, Hanhan; Wang, Guiying; Ma, Xiuliang; Tu, Jiacai; Yang, Lei; Li, Junxia; Wang, Yuxi; Meng, Xueqiang; Zhang, Wenyu; Li, Shenghao; et al. (Frontiers in Veterinary Science, 2025)
This study investigated the effects of 3% (G3), 6% (G6), and 9% (G9) dietary defatted black soldier fly larvae (BSFL) meal on 288 Hy-Line Brown laying hens over 210 days. While egg production and weight showed no significant differences (p > 0.05), feed-to-egg ratios increased in higher inclusion groups (G6, G9) versus 0% control (G0) during later phases (p < 0.01). G6 exhibited enhanced eggshell strength versus G0 (p < 0.05), while G3 demonstrated thicker eggshells than all groups (p < 0.05). Serum analysis revealed G3 had superior total antioxidant capacity and lower lipid peroxidation versus G0 and G9 (p < 0.05), along with elevated gonadotropin-releasing hormone levels compared to G9 (p < 0.05). Intestinal morphology remained unaffected across treatments. The 3% BSFL inclusion optimally balanced eggshell quality and antioxidant status under isoenergetic-isoprotein conditions, supporting its viability as a sustainable protein source in poultry diets. Findings advocate BSFL meal as an eco-friendly feed alternative, with 3% identified as the most effective inclusion rate.